Tocilizumab Exerts Anti-Tumor Effects on Colorectal Carcinoma Cell Xenografts Corresponding to Expression Levels of Interleukin-6 Receptor - Yuan-Chiang Chung; Szu-Jung Chen; Chiu-Chen Huang; Wei-Chun Liu; Ming-Tsung Lai; Ting-Yu Kao; Wei-Shun Yang; Chien-Hui Yang; Chih-Ping Hsu; Jia-Feng Chang (MDPI AG, 2024)
The use of tocilizumab against the interleukin-6 receptor (IL-6R) has been demonstrated as inhibiting the progression of diverse cancers in vitro and in vivo. Nonetheless, evidence regarding the anti-tumor effects of tocilizumab on human colorectal carcinoma (CRC) corresponding to IL-6R expression levels remains scarce. To investigate the influence of IL-6R expression, SW480 and HT-29 cells inoculated subcutaneously into NU/NU mice were used as human CRC xenograft models with anti-IL-6R antibody (tocilizumab) therapy. The IL-6R expression levels, histology of CRC growth/invasiveness, and tumor growth-related signaling pathway were estimated by H&E and immunohistochemical staining. SW480 tumor cells with higher IL-6R expression levels showed better responsiveness in tocilizumab therapy than in the treated HT-29 group. Likewise, therapeutic effects of tocilizumab on the proliferative ability with mitotic index and Ki-67 expressions, invasiveness with MMP-9 proteinase expressions, and ERK 1/2 and STAT3 signaling transduction in the SW480 treatment group were superior to the HT-29 treatment group. In light of our results, IL-6R is the key indicator for the efficacy of tocilizumab treatment in CRC xenografts. From the perspective of precision medicine, tumor response to anti-IL-6R antibody therapy could be predicted on the basis of IL-6R expression levels. In this manner, tocilizumab may serve as a targeted and promising anti-CRC therapy.